IMBANGAN PUPUK ORGANIK DAN ANORGANIK PADA PERTANAMAN WORTEL (Daucus carota L.) DI ANDISOLS TAWANGMANGU - Sumani Sumani; Musthofa Musthofa; Sri Hartati (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2009)
Title : The Balance of Organic and Inorganic Fertilizer on the Carrot Field (Daucus carota L.) at Andisols Tawangmangu. This experiment research was conducted on September – December 2007 in Blumbang, Sub district Tawangmangu, Karanganyar. The aim of this research was to know the effect of balance organic fertilizer and inorganic fertilizer to the carrot quality in Andisols, Tawangmangu. This experiment used RCBD (Randomized Complete Block Design) with organic fertilizer factor (0%, 50% and 100% organic fertilizer) and inorganic fertilizer factor (0%, 50% and 100% inorganic fertilizer). Statistical analysis for the influence of the treatment was variant analysis with F-test and Kruskal-Wallis test. Duncan Multiple Range Test (DMRT) was used to compare inter-treatment and for finding out of the relation inter-variable it was used correlation test. The result shows that the balance of organic and inorganic fertilizer have significant influence to the water content of carrot, the weight of carrot, the weight of dried carrot plant and the plant’s height, and have not significant influence to the carotene, carrot’s diameter, and carrot’s length. The lower water content of carrot was shown by the treatment of 100% organic fertilizer and 50% inorganic fertilizer. The treatment of 100% organic fertilizer and 100% inorganic fertilizer give the highest plant height and the weight of carrot per plant. To the soil, the balance of organic and inorganic fertilizer has significant influence to the total N of soil and to the available N of soil. It has not significant influence to the total P of soil and available P of soil, total K of soil and available K of soil. The result of correlation test showed there was positive correlation among carrot weight and water content of carrot. Keywords: Organic fertilizer, Inorganic Fertilizer, Carrot, Andisols.